2008
DOI: 10.1111/j.1460-9568.2008.06376.x
|View full text |Cite
|
Sign up to set email alerts
|

Tonotopy and inhibition in the midbrain inferior colliculus shape spectral resolution of sounds in neural critical bands

Abstract: Frequency resolution and spectral integration in acoustic perception is investigated psychacoustically by measuring critical bands (CBs) or equivalent quantities. In general, CB bandwidths increase with increasing sound frequency but remain constant over a large range of sound pressure levels (SPL; intensity independence). These CB properties have previously been found, on average, in responses of midbrain inferior colliculus neurons. Here, we use single-neuron recordings from the central nucleus of mouse infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Possible sources of SC auditory selectivity are intrinsic and/or afferent inhibitory circuitry (25)(26)(27). In this study, neurons in dorsal SC showed greatest selectivity to FM stimuli, and previous research suggests that inhibitory interactions may underlie the sharpening of auditory responses to FM sweeps (28)(29)(30).…”
Section: Discussionmentioning
confidence: 63%
“…Possible sources of SC auditory selectivity are intrinsic and/or afferent inhibitory circuitry (25)(26)(27). In this study, neurons in dorsal SC showed greatest selectivity to FM stimuli, and previous research suggests that inhibitory interactions may underlie the sharpening of auditory responses to FM sweeps (28)(29)(30).…”
Section: Discussionmentioning
confidence: 63%
“…Tones within the frequency range of a critical band are thought to activate the same location of the basilar membrane (Schreiner et al, 2000). Critical bands contribute to the ability to discriminate sounds (Ehret and Merzenich, 1988; Schreiner and Langner, 1997; Egorova et al, 2006; Egorova and Ehret, 2008) and to detect sounds in background noise (Watson, 1963). Critical band filtering and integration are basic components of mammalian sound perception (Plomp, 1968; Scharf, 1970; Plomp, 1971; Greenwood, 1991; Roederer, 2008) and are active for any sound composed of complex frequencies, which is almost every natural sound (Scharf, 1970).…”
Section: Anatomy and Physiology Of Critical Bandsmentioning
confidence: 99%
“…The logarithmic scale of critical band frequency dependence implicated the cochlea in determining this feature, since cochlear maps are also logarithmic (Braun, 1997). Intensity independence and linearity are not present peripherally, however, and instead are thought to be represented more centrally, perhaps by midbrain structures (Ehret and Merzenich, 1985; 1988; Egorova and Ehret, 2008). …”
Section: Anatomy and Physiology Of Critical Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common principle of the relationship between excitatory and inhibitory frequency tuning is that frequencies just above and/or below excitatory frequencies often suppress a neuron’s firing, both spontaneous and sound-evoked (Yang et al, 1992; Egorova et al, 2001; Egorova and Ehret, 2008; Mayko et al, 2012; Schneider and Woolley, 2011; Schumacher et al, 2011). This sideband inhibition is functionally similar to lateral inhibition in the visual system in that it sharpens tuning.…”
Section: General Features Of Auditory Processing In Ic and Mldmentioning
confidence: 99%